A commentary quiz: What musical composition best describes a primary contribution of your article?. Issue 1 (February 2016) - Bartunek, Jean M
The contributions in this Special Issue focus on relationships between sensemaking (primarily), learning, and dynamic complexity. They address a range of phenomena, including mindfulness, radical learning, formal inquiries after dealing with natural disasters, adult learning, and big data. While not explicitly framed as such, the contributions can be understood in terms of the musical elements they embody, including sequence, rhythm, punctuation, polyphony, and thematic transformation. In this commentary, I suggest how these musical elements are expressed in the articles. On the basis of these musical elements, I present the musical compositions that describe primary contributions of each article.